Feasibility of 3.5 mm C2 pedicle screws in children: A computerized tomography analysis. Issue 3 (8th February 2022) - Chen, Jiarui; Cen, Jiemei; Ma, Teng; Du, Yuwang; Liang, Tuo; Liao, Shian; Yu, Chaojie; Sun, Xuhua; Li, Jiakun; Jiang, Jie; Chen, Tianyou; Li, Hao; et al.
Abstract: There have been no studies with large sample sizes on growth of the pedicle of C2 in children. In the present study we measured the pedicle of C2 through computed tomography (CT) imaging in children aged less than 14 years and evaluated the suitability of the 3.5‐mm screw for the pedicle in such children. The study was conducted on CT morphometric images of 420 children in our hospital between June 2018 and June 2020. The width (D1), length (D2), height (D3), inclination angle (α), and tail angle (β) of the C2 pedicle were measured. One‐way analysis of variance and Student's t test were used for statistical analyses. The least‐square method was used to analyze the curve fitting the trend of anatomical change in the pedicle. The largest degree of goodness of fit determined the best‐fitting curve. The size of the pedicle of C2 increased with age. The median ranges of D1, D2, D3, α, and β were 3.312–5.431 mm, 11.732–23.645 mm, 3.597–8.038 mm, 32.583°–36.640°, and 24.867°–31.567°, respectively. The curves fitting the trends of D1 and D3 were power functions, whereas D2 was fitted by a logarithmic curve. However, no curve fitted α or β. A 3.5‐mm screw can be placed in the pedicle of C2 in children aged more than 1 year. The growth and development trend of this pedicle can provide an anatomical reference for deciding on posterior cervical surgery and for selecting and designing pedicle screws for children.